2000
DOI: 10.1038/35004599
|View full text |Cite
|
Sign up to set email alerts
|

A clonogenic common myeloid progenitor that gives rise to all myeloid lineages

Abstract: Haematopoietic stem cells give rise to progeny that progressively lose self-renewal capacity and become restricted to one lineage. The points at which haematopoietic stem cell-derived progenitors commit to each of the various lineages remain mostly unknown. We have identified a clonogenic common lymphoid progenitor that can differentiate into T, B and natural killer cells but not myeloid cells. Here we report the prospective identification, purification and characterization, using cell-surface markers and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
2,101
4
23

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,276 publications
(2,217 citation statements)
references
References 29 publications
60
2,101
4
23
Order By: Relevance
“…Stem/progenitor cells present in the marrow of normal mice expresses CD117 50 and are further divided by the CD34 marker, into specific cell subpopulations 51,52 . CD117 expression identifies also stem/progenitor cells in the marrow of mice with the Gata1 low mutation 11,44 .…”
Section: Stem/progenitor Cells From the Marrow And The Blood Of Gata1mentioning
confidence: 99%
“…Stem/progenitor cells present in the marrow of normal mice expresses CD117 50 and are further divided by the CD34 marker, into specific cell subpopulations 51,52 . CD117 expression identifies also stem/progenitor cells in the marrow of mice with the Gata1 low mutation 11,44 .…”
Section: Stem/progenitor Cells From the Marrow And The Blood Of Gata1mentioning
confidence: 99%
“…they repress the production of each other [7-9]. In the erythrocyte/megakaryocite lineage high expression levels of gene GATA-1 and low levels of PU.1 were detected [6,10]; conversely, in the granulocyte/macrophage lineage higher expression levels of PU.1 and low levels of GATA-1 were measured [5,11]. However, the initial progenitor cells stay in the third state that has low-level activation of both genes PU.1 and GATA-1 .…”
Section: Introductionmentioning
confidence: 99%
“…GATA-2 is one of the six members of the hematopoietic GATA factor family and is most abundantly expressed in HSCs as well as in immature progenitors in hematopoietic lineages [10]. Previous studies demonstrated a critical role of GATA-2 in the emergence and maintenance of HSCs [19].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-lineage development from single hematopoietic stem/progenitor cell raises the possibility that multi-or bi-potential lineage cells may exist at various branches of lineage development and that these cells may be able to respond under local conditions to determine their fate. Previous studies have suggested that erythroid and myeloid lineages share common precursor cells (common myeloid progenitors) giving rise to all types of myeloid cells and erythroid cells without lymphocytes [2,3]. A recent report has shown that common myeloid progenitors can be isolated from normal bone marrow using antibodies to cell surface markers, including CD19, CD34, CD45RA, IL-3Rα, and thrombopoietin receptor [4].…”
Section: Introductionmentioning
confidence: 99%